AN CRITICAL VISUAL ANALYSIS OF GENDER STEREOTYPING IN THE INDONESIAN SECONDARY SCHOOL ENGLISH TEXTBOOK - Catur Wulandari; Hastowohadi Hastowohadi; Totok Hari Prasetiyo (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This research was intended to investigate the gender stereotype of thetextbook drawn from an English textbook series used in senior highschool employing a multimodal perspective and critical visual analysis.The study used a descriptive design because the writer wanted to describethe gender stereotype of the English textbook. The object of this study isthe Bahasa Inggris (edisi revisi 2017) textbook. The results of data analysisusing used three aspects of Kress and Van Leeuwen namelyrepresentational meaning, interactive meaning, and compositionalmeaning, the focus of the analysis was on images consisting of malecharacters and women use the theory of